Abdominal Sepsis and Peritonitis: discussion and unsolved questions - P. D. Fomin; S. D. Shapoval; R. I. Sidorchuk (Сучасні медичні технології)
Abdominal sepsis (AS) is one of the most severe complications in abdominal surgery. Mortality from the AS according to various data can reach up to 80–90% depending on the etiology, peculiarities of pathogenesis and comorbidities. Purpose of the study is to determine the current state of the problem of abdominal sepsis, to identify problems and discussion issues and to outline possible perspectives for their solution. AS remains one of the important problems of modern urgent abdominal surgery, and ii is characterized by a large variety of etiological factors and polymorphism of the clinical picture. Changing the paradigm of sepsis (Sepsis-1, 2, 3) requires correction of treatment-diagnostic approaches in patients with acute abdominal surgery. Existing methods of diagnosing and treating abdominal sepsis are not effective enough, and therefore there is a need to improve them and develop new, adequate therapeutic approaches.